STUDI KASUS PEMBERIAN TERAPI RELAKSASI OTOT PROGRESIF DALAM PEMENUHAN KEBUTUHAN SIRKULASI PADA PASIEN HIPERTENSI - Ferlita, Maudy Rose; Sulistyawati, Ririn Afrian; Fitriyani, Noor (Universitas Kusuma Husada Surakarta, 2022)
Hypertension is a public health problem that slowly causes the death of many patients. It is because patients with hypertension does not show visible and specific symptoms. Various factors have roles in increasing blood pressure, including psychological disorders such as stress and anxiety. Patients with elevated blood pressure may be given progressive muscle relaxation techniques. The purpose of this research is to find the description of nursing care in patients with hypertension in the fulfillment of circulation needs. This was descriptive research using case study approach. Subject of the case study was one patient with stage-2 hypertension who was treated in Dahlia Room 8 RST Dr Asmir Salatiga. The subject received progressive muscle relaxation technique twice a day for 20 minutes and it was carried for three consecutive days. The result showed that after receiving the therapy, the patient’s blood pressure decreased from 180/90 mmHg to 120/90 mmHg. Therefore, it can be concluded that progressive muscle relaxation is effective for patients with hypertension.